Diffusion Monte Carlo Calculations of Zero‐Point Energies of Methanol and Deuterated Methanol. Issue 2 (3rd October 2018) - Nandi, Apurba; Qu, Chen; Bowman, Joel M.
Abstract : Diffusion Monte Carlo (DMC) simulations have been used to obtain quantum zero‐point energies of methanol and all its isotopologs and isotopomers, using a new, accurate semi‐global potential energy surface. This potential energy surface is a precise, permutationally invariant fit to 6676 ab initio energies, obtained at the CCSD(T)‐F12b/aug‐cc‐pVDZ level of theory. Quantum zero‐point energies of deuterated methanol isotopomers are very close to each other and so a simple statistical argument can be used to estimate the populations of each isotopomer at very low‐temperatures. The DMC simulations also indicate that there is virtually zero probability for H/D exchange in the zero‐point state. © 2019 Wiley Periodicals, Inc. Abstract : Diffusion Monte Carlo trajectories for indicated isotopologs and isotopomers of methanol.